已知 $a=e-1, b=2-\ln 2, c=e^{e}-e^2+1$, 则
$ \text{A.} $ $c > b > a$ $ \text{B.} $ $a > b > c$ $ \text{C.} $ $a > c > b$ $ \text{D.} $ $c > a > b$
【答案】 D

【解析】 令 $f(x)=x-\ln x, x > 0$,
则 $f(e)=e-\ln e=e-1=a, f(2)=2-$ $\ln 2=b$
$\because f^{\prime}(x)=1-\frac{1}{x}=\frac{x-1}{x}$,
$\therefore$ 当 $x > 1$ 时, $f^{\prime}(x) > 0, f(x)$ 单调递增,
$\therefore f(e) > f(2)$, 即 $a > b$,
令 $g(x)=e^x-x$, 则 $g^{\prime}(x)=e^x-1$,
$\therefore$ 当 $x > 0$ 时, $g^{\prime}(x) > 0, g(x)$ 单调递增,
$\therefore g(e) > g(2)$, 即 $e^e-e > e^2-2$,
所以 $e^e-e^2+1 > e-1$, 即 $c > a$.
综上, $c > a > b$.
故应选 D.
系统推荐